High-solubility lithium-sulfur battery electrolyte and lithium-sulfur battery containing electrolyte
By using high DN phosphoramide solvents with ether solvents to form core-shell structures in lithium-sulfur battery electrolytes, the problems of low solubility of lithium polysulfide and poor interfacial stability of lithium negative electrodes are solved, and high sulfur utilization and long cycle life are achieved effect.
Patent Information
- Application Number
- CN202411597811.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the traditional ether-based electrolyte, the lithium polysulfide has a low solubility, which makes it difficult for sulfur electrodes to obtain higher utilization under electrolyte conditions, limiting the energy density and circulation of lithium sulfur batteries. life.
High DN phosphoramide solvent and ether solvent are used to form a core-shell structure through intermolecular hydrogen bonding, which promotes the dissolution of lithium polysulfide and the stability of free radicals, and improves the reaction kinetics of sulfur and the cyclic stability of lithium negative electrodes.
Under the conditions of high load-bearing electrolyte, the utilization rate of sulfur and the circulation stability of the lithium negative electrode are improved, the cycle life of the battery is extended and the energy density is improved.
Smart Images

Figure CN119481267A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-soluble lithium-sulfur batteries, and in particular relates to a high-soluble lithium-sulfur battery electrolyte and a lithium-sulfur battery containing the electrolyte. Background Art
[0002] In recent years, lithium-ion batteries have occupied an important position in the field of new energy. However, their limited energy density limits their application in civil and military fields such as electric vehicles and drones. Therefore, the development of new high-energy-density battery systems is of great significance to meet the energy and power needs of social production and development. Lithium-sulfur batteries have a theoretical energy density of up to 2600Wh / kg, and sulfur resources are abundant and environmentally friendly. They are one of the most promising high-energy-density battery systems. However, it is still a huge challenge to achieve high energy density and obtain a practical battery technology. Especially in traditional ether-based electrolytes, the solubility of lithium polysulfide is low. In the middle of discharge, high-concentration (even saturated) lithium polysulfide cathode solutions have poor transport characteristics and reaction kinetics, which makes it difficult for sulfur electrodes to obtain high utilization rates under lean electrolyte conditions, thereby reducing the energy density of the battery and limiting the practical application of lithium-sulfur batteries.
[0003] By changing the structural components of the electrolyte to construct a highly soluble electrolyte, the dissolution of lithium polysulfide can be promoted, and its morphological structure can be adjusted to promote its reaction kinetics under lean electrolyte conditions to obtain a higher utilization rate of active substances. Solvent molecules with a high Gutmann donor number (DN), such as dimethylacetamide (DMA, 27.8 kcal / mol), N-dimethylformamide (DMF, 26.6 kcal / mol) and dimethyl sulfoxide (DMSO, 29.8 kcal / mol), have been shown to dissolve higher concentrations of lithium polysulfide and promote the formation of free radicals, thereby improving the conversion efficiency of lithium polysulfide. However, high DN solvents are generally highly corrosive to alkali metals, and it is difficult to form a stable negative electrode interface film during the cycle process, which limits their application in lithium metal batteries.
[0004] CN202211319954.X discloses an electrolyte suitable for a lithium-sulfur battery with a high sulfur surface loading, comprising an organic solvent, a lithium salt and an auxiliary solvent. The electrolyte has a high solubility for lithium polysulfide, thereby improving the conversion rate of lithium polysulfide during the charge and discharge process, and achieving a high active material utilization rate and good rate performance of the lithium-sulfur battery at a high sulfur surface loading.
[0005] At present, the above-mentioned lithium-sulfur battery electrolytes have achieved higher capacity density by promoting the dissolution of lithium polysulfide in high-surface-load electrodes, but the above-mentioned electrolytes still have problems such as poor interface stability of lithium metal negative electrodes and short battery cycle life. Therefore, the development of high-solubility lithium-sulfur battery electrolytes that take into account both the high reactivity of sulfur electrodes and the long cycle stability of lithium metal electrodes is of great significance for promoting the technological development of lithium-sulfur batteries and improving the energy density of batteries under poor electrolyte conditions. Summary of the invention
[0006] The object of the present invention is to provide a highly soluble lithium-sulfur battery electrolyte and a lithium-sulfur battery containing the electrolyte. A highly soluble lithium-sulfur battery electrolyte is proposed: a high-DN phosphoramide solvent promotes the dissolution of lithium polysulfide and stabilizes free radicals, promotes the reaction kinetics of sulfur, and improves the sulfur utilization rate of the battery under high-load lean electrolyte conditions; an ether solvent and phosphoramide form a core-shell structure through intermolecular hydrogen bonds, inhibiting the chemical reaction of lithium metal, thereby solving the problems of poor interface stability of lithium metal negative electrode and short battery cycle life in the existing electrolyte.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A highly soluble lithium-sulfur battery electrolyte comprising a solvent and a lithium salt;
[0009] The solvent includes a main solvent 1 and a main solvent 2;
[0010] The main solvent 1 is composed of one or more ether solvents, and the main solvent 2 is composed of one or more phosphoramide solvents; the phosphoramide solvent and the ether solvent have good compatibility, wherein the phosphoramide has a strong coordination ability with lithium ions, can promote the dissolution of lithium polysulfide, stabilize free radicals, activate the reaction path involving free radicals, thereby improving the reaction kinetics of sulfur and lithium polysulfide, and obtaining a high utilization rate of active substances; the ether solvent has good stability and excellent film-forming ability for the metal lithium negative electrode;
[0011] The main solvent 1 is an ether solvent having a chain or ring molecular structure or a composite solvent composed of the ether solvent, preferably one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, 1,3-dioxolane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether;
[0012] The second main solvent is a phosphoramide solvent, preferably one or more of hexamethylphosphoramide, tris(N,N-tetramethylene)phosphoramide, cyclophosphamide, ifosfamide, triethylenethiophosphoramide, n-propylthiophosphoramide, and n-butylthiophosphoramide.
[0013] The present invention is further preferably characterized in that: the volume fraction of the main solvent, an ether solvent, is 70% to 99%, and the volume fraction of the main solvent, diphosphoramide, is 1% to 30%;
[0014] The lithium salt includes one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(fluoromethylsulfonyl)imide, lithium perchlorate, lithium tetrafluoroborate and lithium hexafluorophosphate;
[0015] The volume molar fraction of the lithium salt is set to 0.1 to 2.0 mol / L.
[0016] The present invention is further preferably provided with a solvent, a lithium salt and an additive.
[0017] The present invention is further preferably characterized in that: the additive comprises lithium nitrate or lithium tetrafluoroborate;
[0018] The mass fraction of the additive is 0.1 to 6% of the total mass of the electrolyte;
[0019] The electrolyte can obtain a higher sulfur utilization rate under high sulfur loading and low electrolyte conditions, and at the same time, the lithium negative electrode has a higher coulombic efficiency. The ether main solvent and the phosphoramide co-solvent in the electrolyte form intermolecular hydrogen bonds during the dissolution process and restrict the phosphoramide solvent to the first solvation shell of lithium ions, thereby inhibiting the corrosion of the phosphoramide solvent on the metal lithium negative electrode and improving the cycle stability of the metal lithium negative electrode.
[0020] The present invention is further preferably provided that the present invention also includes a method for preparing a highly soluble lithium-sulfur battery electrolyte, wherein the highly soluble lithium-sulfur battery electrolyte is prepared by the following method:
[0021] (1) using molecular sieves to remove water from the solvent used, and leaving it to stand for 48 to 72 hours;
[0022] (2) using a glass drying apparatus to dry the lithium salt in a vacuum at a high temperature to remove moisture, the temperature range is between 50 and 120 degrees Celsius, and the drying time is 24 hours;
[0023] (3) mixing the dried solvent 1 with the solvent 2 to obtain a uniform solution;
[0024] (4) Adding the dried lithium salt and additives into the above-mentioned uniform solvent, the highly soluble lithium-sulfur battery electrolyte can be obtained.
[0025] A lithium-sulfur battery using a highly soluble electrolyte comprises a battery cell, wherein the battery cell comprises a positive electrode, a separator, an electrolyte and a negative electrode.
[0026] The present invention is further preferably: the electrolyte is the electrolyte described above;
[0027] The positive electrode material is a sulfur-carbon composite material, wherein the carbon material includes but is not limited to Ketjen black, activated carbon, carbon nanotubes, graphene, carbon fiber, and the mass fraction of sulfur is 50-90%;
[0028] The negative electrode materials include lithium foil, lithium alloy negative electrode, silicon negative electrode, silicon-carbon negative electrode, and lithium-copper composite electrode.
[0029] The present invention is further preferably: the lithium-sulfur battery of the highly soluble electrolyte is prepared by the following method:
[0030] The positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery case in sequence and sealed with a sealing machine.
[0031] The present invention is further preferably: the positive electrode of the lithium-sulfur battery using a highly soluble electrolyte is prepared by the following method;
[0032] The positive electrode material, the conductive agent and the binder are dispersed in a solvent according to a certain mass ratio, mixed evenly, and then evenly coated on the aluminum current collector, and dried to obtain a positive electrode sheet;
[0033] The conductive agent is not limited to one or more of super P, acetylene black, activated carbon, and Ketjen black;
[0034] The binder includes polyvinylidene fluoride, polytetrafluoroethylene, LA133, sodium carboxymethyl cellulose or sodium alginate;
[0035] Select the dispersing solvent according to the type of binder. If polyvinylidene fluoride or polytetrafluoroethylene is used as the binder, use N-methylpyrrolidone as the dispersing liquid. If LA133, sodium carboxymethyl cellulose or sodium alginate is used as the binder, choose deionized water as the dispersing liquid.
[0036] The mass ratio of the positive electrode material, the conductive agent and the binder is 7:2:1 or 8:1:1.
[0037] The present invention has the following beneficial effects:
[0038] 1. The present invention proposes a highly soluble lithium-sulfur battery electrolyte: a high-DN phosphoramide solvent promotes the dissolution of lithium polysulfide and stabilizes free radicals, promotes the reaction kinetics of sulfur, and improves the sulfur utilization rate of the battery under high-load lean electrolyte conditions.
[0039] 2. The electrolyte proposed in the present invention takes into account both the reaction activity of the sulfur electrode and the cycle stability of the lithium negative electrode: phosphoramide usually has a strong corrosive effect on metallic lithium, but ether solvents can easily form intermolecular hydrogen bonds with phosphoramide solvents and restrict phosphoramide to the first solvation sheath, thereby inhibiting the corrosion of phosphoramide to lithium metal and improving the cycle stability of the lithium negative electrode.
[0040] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0042] Figure 1 The charge and discharge curves of the lithium-sulfur battery of Example 1 and Comparative Example 1 under the condition of poor electrolyte are shown.
[0043] Figure 2 This is a cycle performance diagram of the lithium-sulfur battery under poor electrolyte conditions of Example 1 of the present invention and Comparative Example 1.
[0044] Figure 3 This is a charge and discharge curve diagram of the lithium-sulfur battery under poor electrolyte conditions in Example 2 of the present invention.
[0045] Figure 4 The figure shows the rate performance of the lithium-sulfur battery of Example 3 of the present invention and Comparative Example 2.
[0046] Figure 5 This is a cycle performance diagram of the lithium-sulfur battery under poor electrolyte conditions of Example 4 of the present invention.
[0047] Figure 6 This is the first charge and discharge curve of the lithium-sulfur battery of Example 5 of the present invention. DETAILED DESCRIPTION
[0048] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0049] It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs. Specific embodiment 1
[0051] See also Figure 1-2 The present invention is a highly soluble lithium-sulfur battery electrolyte, the electrolyte comprising a main solvent 1, a main solvent 2, a lithium salt and an additive; wherein the main solvent 1 is composed of ethylene glycol dimethyl ether and 1,3-dioxolane, and the main solvent 2 is hexamethylphosphoramide;
[0052] The volume fraction of the main solvent 1 in the electrolyte system is 92%, the volume fraction of the main solvent 2 in the electrolyte system is 8%, the molar concentration of the lithium salt in the electrolyte system is 0.5 mol / L, and the mass fraction of the lithium nitrate additive is 5%;
[0053] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:
[0054] (1) adding a certain amount of molecular sieves to a mixed solvent consisting of a main solvent 1 and a main solvent 2 for dehydration treatment, mixing them evenly and then standing them for standby use, the standing time being 48-72 hours;
[0055] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.
[0056] (3) mixing the dried main solvent 1 and the main solvent 2 in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether, 1,3-dioxolane and hexamethylphosphoric acid triamide in the uniform solution is 46:46:8;
[0057] (4) adding the dried lithium salt and additives to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte (the concentration of lithium bistrifluoromethylsulfonyl imide is 0.5 mol / L, and the mass fraction of lithium nitrate is 5%) after standing for 24 hours;
[0058] A set of lithium-sulfur batteries is assembled using the above-mentioned lithium-sulfur battery electrolyte. The lithium-sulfur battery consists of a battery positive and negative electrode shell and a battery core. The battery core includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery shell in sequence, and the lithium-sulfur battery is obtained after sealing with a sealing machine.
[0059] The positive electrode composition of the lithium-sulfur battery is graphene sulfur-Super P-polyvinylidene fluoride, in which the mass ratio of each component is 8:1:1, and the sulfur loading is 5.5 mg / cm 2 , the electrolyte dosage is 4uL / mg s .
[0060] like Figure 1As shown, the lithium-sulfur battery of Comparative Example 1 exhibits a large overpotential at a rate of 0.1C under the conditions of a sulfur loading of 5.5 mg / cm2 and an electrolyte dosage of 4.0 uL / mgs, indicating a slower kinetics. The lithium-sulfur battery of Example 1 can release a specific capacity of up to 865 mAh / g and a lower overpotential under the same conditions, showing that the electrolyte in Example 1 effectively promotes the reduction process of sulfur under lean electrolyte conditions and improves the utilization rate of sulfur;
[0061] like Figure 2 As shown, the lithium-sulfur battery of Comparative Example 1 exhibits a lower discharge specific capacity and poor cycle stability under the conditions of a sulfur loading of 5.5 mg / cm2 and an electrolyte dosage of 4.0 uL / mgs, indicating that sulfur in conventional electrolytes has poor kinetics. The lithium-sulfur battery of Example 1 has a capacity retention rate of up to 86% after 65 cycles at a rate of 0.1C under the same conditions, demonstrating the good interface stability of the negative electrode of the electrolyte of Example 1 under lean electrolyte conditions. Specific embodiment 2
[0063] See also Figure 3 The present invention is a highly soluble lithium-sulfur battery electrolyte, the electrolyte comprising a main solvent 1, a main solvent 2, a lithium salt and an additive; wherein the main solvent 1 is composed of ethylene glycol dimethyl ether and 1,3-dioxolane, and the main solvent 2 is tris (N, N-tetramethylene) phosphoramide;
[0064] The volume fraction of the main solvent 1 in the electrolyte system is 90%, the volume fraction of the main solvent 2 in the electrolyte system is 10%, the molar concentration of the lithium salt in the electrolyte system is 0.5 mol / L, and the mass fraction of the lithium nitrate additive is 5%;
[0065] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:
[0066] (1) adding a certain amount of molecular sieves to a mixed solvent consisting of a main solvent 1 and a main solvent 2 for dehydration treatment, mixing them evenly and then standing them for standby use, the standing time being 48-72 hours;
[0067] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.
[0068] (3) mixing the dried main solvent 1 and the main solvent 2 in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether, 1,3-dioxolane and tris(N,N-tetramethylene)phosphoramide in the uniform solution is 45:45:10;
[0069] (4) adding the dried lithium salt and additives to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte (the concentration of lithium bistrifluoromethylsulfonyl imide is 0.5 mol / L, and the mass fraction of lithium nitrate is 5%) after standing for 24 hours;
[0070] A set of lithium-sulfur batteries is assembled using the above-mentioned lithium-sulfur battery electrolyte. The lithium-sulfur battery consists of a battery positive and negative electrode shell and a battery core. The battery core includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery shell in sequence, and the lithium-sulfur battery is obtained after sealing with a sealing machine.
[0071] The positive electrode composition of the lithium-sulfur battery is graphene sulfur-Super P-polyvinylidene fluoride, in which the mass ratio of each component is 8:1:1, the sulfur loading is 3.5 mg / cm2, and the electrolyte dosage is 5uL / mgs.
[0072] like Figure 3 As shown, the electrolyte of Example 2 is used in a lithium-sulfur battery. Under the conditions of a sulfur loading of 3.5 mg / cm2 and an electrolyte dosage of 5.0 uL / mgs, the battery can release a specific capacity of up to 1192 mAh / g at a rate of 0.05C, demonstrating that the electrolyte of Example 2 effectively improves the utilization rate of sulfur under lean electrolyte conditions. Specific embodiment 3
[0074] See also Figure 4 The present invention is a highly soluble lithium-sulfur battery electrolyte, the electrolyte comprising a main solvent 1, a main solvent 2, a lithium salt and an additive; wherein the main solvent 1 is composed of ethylene glycol dimethyl ether and 1,3-dioxolane, and the main solvent 2 is hexamethylphosphoramide;
[0075] The volume fraction of the main solvent 1 in the electrolyte system is 90%, the volume fraction of the main solvent 2 in the electrolyte system is 10%, the molar concentration of the lithium salt in the electrolyte system is 1 mol / L, and the mass fraction of the lithium nitrate additive is 2%;
[0076] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:
[0077] (1) adding a certain amount of molecular sieves to a mixed solvent consisting of a main solvent 1 and a main solvent 2 for dehydration treatment, mixing them evenly and then standing them for standby use, the standing time being 48-72 hours;
[0078] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.
[0079] (3) mixing the dried main solvent 1 and the main solvent 2 in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether, 1,3-dioxolane and hexamethylphosphoric acid triamide in the uniform solution is 45:45:10;
[0080] (4) adding the dried lithium salt and additives to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte (the concentration of lithium bistrifluoromethylsulfonyl imide is 1.0 mol / L, and the mass fraction of lithium nitrate is 2%) after standing for 24 hours;
[0081] A set of lithium-sulfur batteries is assembled using the above-mentioned lithium-sulfur battery electrolyte. The lithium-sulfur battery consists of a battery positive and negative electrode shell and a battery core. The battery core includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery shell in sequence, and the lithium-sulfur battery is obtained after sealing with a sealing machine.
[0082] The positive electrode composition of the lithium-sulfur battery is graphene sulfur-Super P-polyvinylidene fluoride, in which the mass ratio of each component is 8:1:1, the sulfur loading is 3.2 mg / cm2, and the electrolyte dosage is 10uL / mgs.
[0083] like Figure 4 As shown, the lithium-sulfur battery of Comparative Example 2 shows a lower discharge specific capacity of only 400 mAh / g at a rate of 3.0C under the conditions of a sulfur loading of 3.2 mg / cm2 and an electrolyte dosage of 10.0 uL / mgs. The lithium-sulfur battery of Example 3 can release a specific capacity of up to 789.1 mAh / g at a rate of 3C under the same conditions, showing that the electrolyte of Example 3 has a higher rate characteristic for lithium-sulfur batteries, indicating that the high-soluble lithium-sulfur battery electrolyte effectively promotes the reaction kinetics of sulfur under high rate conditions. Specific embodiment 4
[0085] See also Figure 5 The present invention is a highly soluble lithium-sulfur battery electrolyte, the electrolyte comprising a main solvent 1, a main solvent 2, a lithium salt and an additive; wherein the main solvent 1 is composed of ethylene glycol dimethyl ether and 1,3-dioxolane, and the main solvent 2 is tris (N, N-tetramethylene) phosphoramide;
[0086] The volume fraction of the main solvent 1 in the electrolyte system is 90%, the volume fraction of the main solvent 2 in the electrolyte system is 10%, the molar concentration of the lithium salt in the electrolyte system is 0.8 mol / L, and the mass fraction of the lithium nitrate additive is 4%;
[0087] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:
[0088] (1) adding a certain amount of molecular sieves to a mixed solvent consisting of a main solvent 1 and a main solvent 2 for dehydration treatment, mixing them evenly and then standing them for standby use, the standing time being 48-72 hours;
[0089] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.
[0090] (3) mixing the dried main solvent 1 and the main solvent 2 in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether, 1,3-dioxolane and tris(N,N-tetramethylene)phosphoramide in the uniform solution is 45:45:10;
[0091] (4) adding the dried lithium salt and additives to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte (the concentration of lithium bistrifluoromethylsulfonyl imide is 0.8 mol / L, and the mass fraction of lithium nitrate is 4%) after standing for 24 hours;
[0092] A set of lithium-sulfur batteries is assembled using the above-mentioned lithium-sulfur battery electrolyte. The lithium-sulfur battery consists of a battery positive and negative electrode shell and a battery core. The battery core includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery shell in sequence, and the lithium-sulfur battery is obtained after sealing with a sealing machine.
[0093] The positive electrode composition of the lithium-sulfur battery is graphene sulfur-Super P-polyvinylidene fluoride, in which the mass ratio of each component is 8:1:1, the sulfur loading is 3.5 mg / cm2, and the electrolyte dosage is 5uL / mgs.
[0094] like Figure 5 As shown, the electrolyte of Example 4 is used in a lithium-sulfur battery. Under the conditions of a sulfur loading of 3.5 mg / cm2 and an electrolyte dosage of 5.0 uL / mgs, the battery can release up to 1191 mAh / g at a rate of 0.05C, and the capacity retention rate is as high as 70.9% after 70 cycles, demonstrating the good interface stability of the negative electrode of the electrolyte of Example 4 under lean electrolyte conditions. Specific embodiment 5
[0096] See also Figure 6 The present invention is a highly soluble lithium-sulfur battery electrolyte, the electrolyte comprising a main solvent 1, a main solvent 2, a lithium salt and an additive; wherein the main solvent 1 is composed of ethylene glycol dimethyl ether and 1,3-dioxolane, and the main solvent 2 is hexamethylphosphoramide;
[0097] The volume fraction of the main solvent 1 in the electrolyte system is 92%, the volume fraction of the main solvent 2 in the electrolyte system is 8%, the molar concentration of the lithium salt in the electrolyte system is 0.5 mol / L, and the mass fraction of the lithium nitrate additive is 6%;
[0098] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:
[0099] (1) adding a certain amount of molecular sieves to a mixed solvent consisting of a main solvent 1 and a main solvent 2 for dehydration treatment, mixing them evenly and then standing them for standby use, the standing time being 48-72 hours;
[0100] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.
[0101] (3) mixing the dried main solvent 1 and the main solvent 2 in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether, 1,3-dioxolane and tris(N,N-tetramethylene)phosphoramide in the uniform solution is 46:46:8;
[0102] (4) adding the dried lithium salt and additives to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte (the concentration of lithium bistrifluoromethylsulfonyl imide is 0.5 mol / L, and the mass fraction of lithium nitrate is 6%) after standing for 24 hours;
[0103] The above-mentioned lithium-sulfur battery electrolyte is used to assemble a soft-pack lithium-sulfur battery. The lithium-sulfur battery consists of an aluminum-plastic film and a battery cell. The battery cell includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator and lithium metal negative electrode are stacked in sequence and placed in the aluminum-plastic film, and the electrolyte is injected to seal. After standing for 24 hours, the lithium-sulfur battery is vacuum-sealed to obtain a lithium-sulfur battery.
[0104] The positive electrode composition of the above-mentioned lithium-sulfur battery is graphene sulfur-Super P-LA133, in which the mass ratio of each component is 85:10:5, the single-sided sulfur loading is 4.6 mg / cm2, and the electrolyte dosage is 4uL / mgs.
[0105] like Figure 6 As shown, the electrolyte of Example 5 is used in a soft-pack lithium-sulfur battery. Under the condition that the electrolyte dosage is 4.0uL / mgs, the battery can obtain a capacity of 2.7Ah, and the energy density can be as high as 307Wh / kg calculated based on the total mass of the battery. This shows the advantages of the electrolyte of Example 5 in building a high energy density lithium-sulfur battery.
[0106] Comparative Example 1
[0107] The electrolyte comprises a main solvent, a lithium salt and an additive; wherein the main solvent is composed of ethylene glycol dimethyl ether and 1,3-dioxolane;
[0108] The molar concentration of the lithium salt in the electrolyte system is 0.5 mol / L, and the mass fraction of the lithium nitrate additive is 5%;
[0109] (1) A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:
[0110] The sub-sieves are added to the main solvent for dehydration treatment, mixed evenly and then allowed to stand for use for 48-72 hours;
[0111] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.
[0112] (3) mixing the dried solvents to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether, 1,3-dioxolane and hexamethylphosphoric acid triamide is 50:50;
[0113] (4) adding the dried lithium salt and additives to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte (the concentration of lithium bistrifluoromethylsulfonyl imide is 0.5 mol / L, and the mass fraction of lithium nitrate is 5%) after standing for 24 hours;
[0114] A set of lithium-sulfur batteries is assembled using the above-mentioned lithium-sulfur battery electrolyte. The lithium-sulfur battery consists of a battery positive and negative electrode shell and a battery core. The battery core includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery shell in sequence, and the lithium-sulfur battery is obtained after sealing with a sealing machine.
[0115] The positive electrode composition of the lithium-sulfur battery is graphene sulfur-Super P-polyvinylidene fluoride, in which the mass ratio of each component is 8:1:1, and the sulfur loading is 5.5 mg / cm 2 , the electrolyte dosage is 4uL / mgs.
[0116] Comparative Example 2
[0117] The electrolyte comprises a main solvent, a lithium salt and an additive; wherein the main solvent is composed of ethylene glycol dimethyl ether and 1,3-dioxolane;
[0118] The molar concentration of the lithium salt in the electrolyte system is 1 mol / L, and the mass fraction of the lithium nitrate additive is 2%;
[0119] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:
[0120] (1) Add a certain amount of molecules to the main solvent for dehydration treatment, mix them evenly and let them stand for use. The standing time is 48-72 hours;
[0121] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.
[0122] (3) mixing the dried main solvent in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether, 1,3-dioxolane and hexamethylphosphoric acid triamide in the uniform solution is 50:50;
[0123] (4) adding the dried lithium salt and additives to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte (the concentration of lithium bistrifluoromethylsulfonyl imide is 1.0 mol / L, and the mass fraction of lithium nitrate is 2%) after standing for 24 hours;
[0124] A set of lithium-sulfur batteries is assembled using the above-mentioned lithium-sulfur battery electrolyte. The lithium-sulfur battery consists of a battery positive and negative electrode shell and a battery core. The battery core includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery shell in sequence, and the lithium-sulfur battery is obtained after sealing with a sealing machine.
[0125] The positive electrode composition of the lithium-sulfur battery is graphene sulfur-Super P-polyvinylidene fluoride, in which the mass ratio of each component is 8:1:1, and the sulfur loading is 3.2 mg / cm 2 , the electrolyte dosage is 10uL / mg s .
[0126] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0127] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A highly soluble lithium-sulfur battery electrolyte, characterized in that: including a solvent and a lithium salt; The solvent includes a main solvent 1 and a main solvent 2; The main solvent 1 is composed of one or more ether solvents, and the main solvent 2 is composed of one or more phosphoramide solvents; The main solvent 1 is an ether solvent having a chain or ring molecular structure or a composite solvent composed of the ether solvent, preferably one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, 1,3-dioxolane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether; The second main solvent is a phosphoramide solvent, preferably one or more of hexamethylphosphoramide, tris(N,N-tetramethylene)phosphoramide, cyclophosphamide, ifosfamide, triethylenethiophosphoramide, n-propylthiophosphoramide, and n-butylthiophosphoramide.
2. A highly soluble lithium-sulfur battery electrolyte according to claim 1, characterized in that: The volume fraction of the main solvent, an ether solvent, is 70% to 99%, and the volume fraction of the main solvent, diphosphoramide, is 1% to 30%; The lithium salt includes one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(fluoromethylsulfonyl)imide, lithium perchlorate, lithium tetrafluoroborate and lithium hexafluorophosphate; The volume molar fraction of the lithium salt is set to 0.1-2.0 mol / L.
3. A highly soluble lithium-sulfur battery electrolyte according to claim 1, characterized in that: Including solvents, lithium salts and additives.
4. A highly soluble lithium-sulfur battery electrolyte according to claim 3, characterized in that: The additive includes lithium nitrate or lithium tetrafluoroborate; The mass fraction of the additive is 0.1-6% of the total mass of the electrolyte.
5. The method for preparing a highly soluble lithium-sulfur battery electrolyte according to claims 1-4, characterized in that: The highly soluble lithium-sulfur battery electrolyte is prepared by the following method: (1) using molecular sieves to remove water from the solvent used, and leaving it to stand for 48 to 72 hours; (2) using a glass drying apparatus to dry the lithium salt in a vacuum at a high temperature to remove moisture, the temperature range is between 50 and 120 degrees Celsius, and the drying time is 24 hours; (3) mixing the dried solvent 1 with the solvent 2 to obtain a uniform solution; (4) Adding the dried lithium salt and additives into the above-mentioned uniform solvent, the highly soluble lithium-sulfur battery electrolyte can be obtained.
6. A lithium-sulfur battery using a highly soluble electrolyte, characterized in that: The lithium-sulfur battery comprises a battery cell, and the battery cell comprises a positive electrode, a separator, an electrolyte and a negative electrode.
7. A lithium-sulfur battery using a highly soluble electrolyte according to claim 6, characterized in that: The electrolyte is the electrolyte in claims 1-4; The positive electrode material is a sulfur-carbon composite material, wherein the carbon material includes but is not limited to Ketjen black, activated carbon, carbon nanotubes, graphene, carbon fiber, and the mass fraction of sulfur is 50-90%; The negative electrode materials include lithium foil, lithium alloy negative electrode, silicon negative electrode, silicon-carbon negative electrode, and lithium-copper composite electrode.
8. A lithium-sulfur battery using a highly soluble electrolyte according to claim 7, characterized in that: The lithium-sulfur battery of the highly soluble electrolyte is prepared by the following method: The positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery case in sequence and sealed with a sealing machine.
9. A lithium-sulfur battery using a highly soluble electrolyte according to claim 8, characterized in that: The positive electrode of the lithium-sulfur battery using a highly soluble electrolyte is prepared by the following method; The positive electrode material, the conductive agent and the binder are dispersed in a solvent according to a certain mass ratio, mixed evenly, and then evenly coated on the aluminum current collector, and dried to obtain a positive electrode sheet; The conductive agent is not limited to one or more of super P, acetylene black, activated carbon, and Ketjen black; The binder includes polyvinylidene fluoride, polytetrafluoroethylene, LA133, sodium carboxymethyl cellulose or sodium alginate; The mass ratio of the positive electrode material, the conductive agent and the binder is 7:2:1 or 8:1:1.
Citation Information
Patent Citations
Electrolyte of high-sulfur surface load lithium-sulfur battery and high-sulfur surface load lithium-sulfur battery
CN115472914A
Lithium-sulfur battery electrolyte, preparation method thereof and lithium-sulfur battery
CN114447426A
Electrolyte for lithium sulphur cell and lithium sulphur cell containing the same electrolyte
CN1335653A
An Electrolyte for Lithium-Sulfur Batteries andLithium-Sulfur Batteries Comprising The Same
KR1020050038895A
Electrolyte solution for lithium-sulfur battery and lithium-sulfur battery comprising same
WO2019212153A1